Survey of X-Rays from Massive Stars Observed at High Spectral Resolution with Chandra - Pragati Pradhan; David P. Huenemoerder; Richard Ignace; Joy S. Nichols; A. M. T. Pollock (The Astrophysical Journal, 2023)
Identifying trends between observational data and the range of physical parameters of massive stars is a critical step to the still-elusive full understanding of the source, structure, and evolution of X-ray emission from the stellar winds, requiring a substantial sample size and systematic analysis methods. As of 2022, the Chandra data archive contains 37 high-resolution spectra of O, B, and WR stars, observed with the Chandra/HETGS, and of sufficient quality to fit the continua and emission-line profiles. Using a systematic approach to the data analysis, we explore morphological trends in the line profiles (i.e., O, Ne, Mg, and Si) and find that the centroid offsets of resolved lines versus wavelength can be separated in three empirically defined groups based on the amount of line broadening and centroid offset. Using Fe xvii (15.01, 17.05 Å) and Ne x α (12.13 Å) lines, which are prevalent among the sample stars, we find a well-correlated linear trend of increasing Full Width Half Maximum with faster wind terminal velocity. The H-like/He-like total line flux ratio for strong lines displays different trends with spectral class depending on ion species. Some of the sources in our sample have peculiar properties (e.g., magnetic and γ Cas-analog stars) and we find that these sources stand out as outliers from more regular trends. Finally, our spectral analysis is presented summarily in terms of X-ray spectral energy distributions in specific luminosity for each source, including tables of line identifications and fluxes.